Additive manufactured customizable labware for biotechnological purposes. Issue 8 (4th August 2017) - Raddatz, Lukas; de Vries, Ingo; Austerjost, Jonas; Lavrentieva, Antonina; Geier, Dominik; Becker, Thomas; Beutel, Sascha; Scheper, Thomas
Abstract : Yet already developed in the 1980s, the rise of 3D printing technology did not start until the beginning of this millennium as important patents expired, which opened the technology to a whole new group of potential users. One of the first who used this manufacturing tool in biotechnology was Lücking et al. in 2012, demonstrating potential uses1 2 . This study shows applications of custom‐built 3D‐printed parts for biotechnological experiments. It gives an overview about the objects' computer‐aided design (CAD) followed by its manufacturing process and basic studies on the used printing material in terms of biocompatibility and manageability. Using the stereolithographic (SLA) 3D‐printing technology, a customizable shake flask lid was developed, which was successfully used to perform a bacterial fed‐batch shake flask cultivation. The lid provides Luer connectors and tube adapters, allowing both sampling and feeding without interrupting the process. In addition, the digital blueprint the lid is based on, is designed for a modular use and can be modified to fit specific needs. All connectors can be changed and substituted in this CAD software‐based file. Hence, the lid can be used for other applications, as well. The used printing material was tested for biocompatibility and showed no toxic effects neither on mammalian, nor on bacteria cells. Furthermore an SDS‐PAGE‐comb was drawn and printed and its usability evaluated to demonstrate the usefulness of 3D printing for everyday labware. The used manufacturing technique for the comb (multi jet printing, MJP) generates highly smooth surfaces, allowing this application.